ENHANCING NATIONAL INNOVATION FRAMEWORKS THROUGH OPEN INNOVATION: A THEORETICAL APPROACH TO INTEGRATING OPEN INNOVATION PRINCIPLES INTO THE EUROPEAN INNOVATION SCOREBOARD (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Despite the growing prominence of Open Innovation (OI) in business and policy, National Innovation Metrics (NIM) remain largely rooted in traditional, firm-centric models, failing to capture ecosystem-wide collaboration and knowledge exchange This study critically examines how OI is integrated - or overlooked - within major Innovation Measurement Frameworks (IMF), particularly the European Innovation Scoreboard (EIS), Global Innovation Index (GII), and Bloomberg Innovation Index (BII). Findings reveal that existing innovation scoreboards prioritize input-output indicators (e.g., R&D expenditure, patenting) while neglecting systemic, network-driven innovation dynamics. The continued absence of OI-specific metrics reinforces a "black box" effect, where national innovation success is assessed without visibility into knowledge flows and collaborative innovation mechanisms. This study contributes to rethinking NIM by advocating for a shift from closed-system assessments to dynamic, network-based measurement models. By bridging innovation policy, measurement theory, and OI research, it provides a foundation for future empirical studies on integrating OI indicators into national benchmarking frameworks, ensuring more accurate assessments of Innovation Ecosystem (IE) performance.